Preparation method of high-sensitivity epinephrine electrochemical detection electrode
Through the electrochemical sensor of Fe@Cu(BTC)/SC-Ti3C2 composite material, the problem of easy oxidation and stacking of Ti3C2 nanosheets is solved, and high sensitivity and stability of adrenaline detection is achieved, with a wide linear range and low detection limits and strong anti-interference ability, suitable for actual medical diagnosis and drug monitoring.
Patent Information
- Application Number
- CN202411453470.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-13
AI Technical Summary
Ti3C2 nanosheets are easily oxidized at room temperature and the strong π-π* interaction leads to stacking, affecting their electrochemical properties. It is difficult for traditional detection methods to achieve high sensitivity and stability of adrenaline detection.
Using Fe@Cu(BTC)/SC-Ti3C2 composite material, the bimetallic organic frame with core-shell structure is combined with two-dimensional layered transition metal carbides to form electrochemistry with high electrocatalytic activity and fast charge/proton transfer rate. Sensor, avoiding material stacking and enhancing dispersion.
It achieves a wide linear range, low detection limit and strong anti-interference ability, and shows high recovery and stability in actual sample detection, improving the sensitivity and accuracy of adrenaline detection.
Smart Images

Figure CN119125269A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to a method for preparing a highly sensitive adrenaline electrochemical detection electrode. Background Art
[0002] Epinephrine (EP), as an important neurotransmitter and hormone in the catecholamine family, plays a vital role in the regulation of the central nervous system of mammals. When an organism faces stressful situations, the existence of EP is particularly critical and can maintain a dynamic balance between blood pressure and blood sugar. For this reason, EP, as a drug widely used in emergency scenarios, can enhance the contractility of the heart in emergencies, promote vasodilation of the heart, tendons and bones, and constrict blood vessels in the skin and mucous membranes. However, once the concentration of EP deviates from the normal range, it may induce a series of diseases, including but not limited to Parkinson's disease, pheochromocytoma, Alzheimer's disease and hypertension. Therefore, real-time monitoring of the EP content in the human body is particularly urgent and important.
[0003] Compared with traditional detection methods, electrochemical sensors have gradually become a research hotspot due to their advantages such as convenient operation, rapid detection, and low cost. In order to develop high-performance EP electrochemical sensors, many nanomaterials are considered as potential modified materials.
[0004] Fe(BTC) and Cu(BTC) are composed of two inexpensive and easy-to-synthesize metal ions and organic ligands. They are not only low-cost, non-toxic, and biocompatible, but also show excellent dispersibility, high catalytic activity (thanks to the presence of a large number of unsaturated metal sites) and excellent biodegradability. Their applications in bio-related fields are becoming increasingly widespread and attracting much attention. By adopting the core-shell strategy, these two different types of MOFs are cleverly combined, in which Cu(BTC) plays a core catalytic role as the "core layer", while Fe(BTC) serves as the "shell layer", which has multiple functions of protection, increasing active sites, and assisting catalysis. This combination not only gives the bimetallic organic framework (Fe@Cu(BTC)) superior performance over single-component MOFs, but also effectively avoids the mutual accumulation of the two components, promotes the uniform dispersion of the components, and forms a unique core-shell structure. In addition, the core-shell structure MOFs provide a variety of charge transfer channels through the closely interwoven heterogeneous interfaces between different MOFs, further accelerating the charge transfer during the reaction process.
[0005] Ti3C2, as an emerging two-dimensional layered transition metal carbide, has shown great application potential in the field of electrochemistry due to its graphene-like properties and unique morphological characteristics. Compared with traditional carbon materials, Ti3C2 nanosheets have better metallic conductivity (up to 10000S / cm), chemical stability, large specific surface area (98m2 / g), excellent biocompatibility and unique hydrophilic properties, which are not possessed by other carbon materials. With its unique advantages, Ti3C2 is often regarded as an ideal electrochemical substrate material. However, the strong π-π* interaction between Ti3C2 nanosheets easily leads to serious stacking. At the same time, the rich functional groups on the surface of Ti3C2 make it difficult to store stably at room temperature and are easily oxidized, thus affecting its performance. Therefore, a method for preparing a highly sensitive adrenaline electrochemical detection electrode is proposed to solve the above problems. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a highly sensitive adrenaline electrochemical detection electrode to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a highly sensitive adrenaline electrochemical detection electrode, comprising the following steps:
[0008] S1. 1.5 g of LiF was dispersed in 60 mL of 9 M HCl solution, and stirred at room temperature until the white powder was completely dissolved. Then, 1.5 g of MAX (Ti3Al C2) was added to the above solution in small amounts and several times, and slowly stirred at 40 ° C for 48 h. The obtained black suspension was washed with distilled water several times until the pH of the solution reached neutrality. Finally, the obtained precipitate was dispersed in 300 mL of distilled water, and ultrasonicated in an ice bath and N2 atmosphere for 1 h to obtain a black suspension, which was freeze-dried to obtain Ti3Al C2 nanosheets with a few-layer structure.
[0009] S2. 0.80 mmol H3BTC was dissolved in 20 mL ethanol solution to obtain solution A, 0.5 g PVP was dissolved in 10 mL distilled water to obtain solution B, 1.43 mmol Cu(NO3)2·3H2O was dispersed in 10 mL distilled water to obtain solution C, solution B was added dropwise to solution A, stirred at room temperature for 2 h to form a transparent solution, solution C was added to the above transparent solution, stirred for 15 min to obtain a blue solution, and finally, it was transferred to a reactor to react under preset reaction conditions, after the reaction, waited to cool to room temperature, the obtained blue precipitate was washed with distilled water, and dried under preset drying conditions to obtain Cu(BTC);
[0010] S3. Disperse 30 mg Cu (BTC) in 20 mL water, ultrasonicate for 30 min, add 20 mL 30 mg PVP solution, stir continuously at room temperature for 24 h, then add 0.15 mmol Fe (NO3) 3 · 9H2O and 0.06 mmol H3BTC to the above solution, continue stirring for 2 h, pour the above mixed solution into a three-necked flask for reaction, then centrifuge and wash, vacuum dry the obtained orange precipitate to obtain Fe@Cu (BTC) / SC-Ti3C2 composite material, add 0.15 mmol Fe (NO3) 3 · 9H2O and 0.06 mmol H3BTC to the above solution in 20 mL 30 mg PVP solution, continue stirring for 2 h, pour the above mixed solution into a three-necked flask for reaction, then centrifuge and wash, vacuum dry the obtained orange precipitate to obtain Fe (BTC);
[0011] S4. 20 mg Ti3C2, 400 mg SC and 10 mg Fe@Cu (BTC) were dispersed in 20 mL distilled water, respectively, and ultrasonicated for 1 h. Then, the SC solution was added dropwise to the Ti3C2 solution, and heated in an oil bath. The Fe@Cu (BTC) solution was added to the mixed solution, and heated in an oil bath to obtain a black suspension. After the protective gas was filled, vacuum filtration was performed to obtain a black precipitated Fe@Cu (BTC) / SC-Ti3C2 composite material;
[0012] S5. Mix the above 2.5 mg of Fe@Cu(BTC) / SC-Ti3C2 black powder with 0.5 mL of 10% The solutions were mixed and ultrasonicated for 30 min to form a uniform black suspension. 8 μL of the suspension was pipetted with a pipette and dropped onto the pretreated GCE surface. The suspension was allowed to stand and dry at room temperature to obtain Fe@Cu(BTC) / SC-Ti3C2 / GCE.
[0013] Preferably, in S2, the reaction temperature of the preset reaction conditions is 100° C., and the reaction time is 7 hours.
[0014] Preferably, in S2, the drying temperature of the preset drying conditions is 80° C., and the drying time is 12 hours.
[0015] Preferably, in S1, the mass ratio of MAX(Ti3AlC2) to LiF is 1:1.
[0016] Preferably, in S3, the reaction temperature is 95° C. and the reaction time is 12 h.
[0017] Preferably, in S4, the heating temperature of the oil bath condition is 120° C., and the heating time is 10 min.
[0018] Preferably, in S4, the protective gas is N2.
[0019] Preferably, in S5, the pretreatment comprises washing with ethanol and distilled water in sequence.
[0020] A method for applying a highly sensitive adrenaline electrochemical detection electrode comprises applying the detection electrode prepared by the above preparation method to detecting adrenaline.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The novel Fe@Cu(BTC) / SC-Ti3C2 composite material-based electrochemical sensor prepared by the present invention has higher electrocatalytic activity and faster charge / proton transfer rate, exhibits good electrochemical sensing performance for detecting EP, a wide linear range of 0.006–300 μM, a low detection limit of 0.0018 μM, strong anti-interference ability and excellent test stability, and the electrochemical sensor also exhibits a satisfactory recovery rate of 99.45-103.10% in actual sample detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 a and Figure 1 b XRD patterns of Fe@Cu(BTC) and Ti3C2, SC-Ti3C2 and Fe@Cu(BTC) / SC-Ti3C2, respectively;
[0024] Figure 2 FT-IR images of Ti3C2, SC-Ti3C2, Fe@Cu(BTC) and Fe@Cu(BTC) / SC-Ti3C2;
[0025] Figure 3 a) and b) are TEM images of Ti3C2; Figure 3 c) is the SEM image of SC-Ti3C2;
[0026] Figure 4 a) SEM images of Cu(BTC), b) Fe(BTC) and c) Fe@Cu(BTC), d) and e) are the SEM magnified image and TEM image of Fe@Cu(BTC), respectively, and f) is the EDS image of Fe@Cu(BTC) / SC-Ti3C2;
[0027] Figure 5 a)- Figure 5 f) SEM image of Fe@Cu(BTC) / SC-Ti3C2 and the corresponding mapping image;
[0028] Figure 6Electrochemical impedance spectroscopy of a) and b) Cu(BTC), Fe(BTC), Fe@Cu(BTC), Ti3C2, SC-Ti3C2 and Fe@Cu(BTC) / SC-Ti3C2 in 5 mM [Fe(CN)6]3- / 4- mixed solution containing 0.1 M KCl;
[0029] Figure 7 a) is the DPV curve of different components in 0.1MPBS (pH=6.0): Cu(BTC), Fe(BTC), Fe@Cu(BTC), Ti3C2, SC-Ti3C2 and Fe@Cu(BTC) / SC-Ti3C2 detecting 60μM EP; b) is the DPV curve of Fe@Cu(BTC) / SC-Ti3C2 detecting 10-60μM EP; c) is the linear relationship between catalytic current and EP concentration;
[0030] Figure 8 Schematic diagram of DPV curve of continuous detection of EP of Fe@Cu(BTC) / SC-Ti3C2 in 0.1M PBS (pH=6.0);
[0031] Fig. 9 a) Schematic diagram of the current-time curve of Fe@Cu(BTC) / SC-Ti3C2 detecting 50μM EP and 500μM interfering substances: tyrosine, glutathione, ascorbic acid, glucose, nicotinamide adenine dinucleotide, L-isoleucine, folic acid and alanine in 0.1M PBS (pH=6.0); b) It curve of Fe@Cu(BTC) / SC-Ti3C2 electrode detecting 10μM EP for 16 hours continuously; c) Bar graph of the long-term stability test of Fe@Cu(BTC) / SC-Ti3C2 electrode;
[0032] Fig.10 a) Schematic diagram of the DPV curve of the same Fe@Cu(BTC) / SC-Ti3C2 electrode detecting 60μM EP six times; b) Schematic diagram of the DPV curve of five identical Fe@Cu(BTC) / SC-Ti3C2 electrodes detecting 60μM EP;
[0033] Fig.11 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] See also Figure 1-Figure 11 As shown, the present invention provides the following technical solutions:
[0036] A method for preparing a highly sensitive adrenaline electrochemical detection electrode comprises the following steps:
[0037] In the present invention, Ti3C2 nanosheets are first prepared, which specifically includes the following steps:
[0038] 1.5 g of LiF was dispersed in 60 mL of 9 M HCl solution and stirred at room temperature until the white powder was completely dissolved.
[0039] 1.5 g of MAX (Ti3AlC2) was added to the above solution in small amounts and stirred slowly at 40°C for 48 hours.
[0040] The obtained black suspension was washed with distilled water several times until the pH of the solution reached neutral.
[0041] The precipitate was dispersed in 300 mL of distilled water and ultrasonicated for 1 h under an ice bath and N2 atmosphere to obtain a black suspension.
[0042] Freeze-drying treatment was performed to obtain Ti3C2 nanosheets with a few-layer structure.
[0043] Then, Cu(BTC) is prepared, which specifically includes the following steps:
[0044] 0.80 mmol H3BTC was dissolved in 20 mL ethanol solution to obtain solution A.
[0045] 0.5 g of PVP was dissolved in 10 mL of distilled water to obtain solution B.
[0046] Disperse 1.43 mmol Cu(NO3)2·3H2O in 10 mL of distilled water to obtain solution C.
[0047] Solution B was added dropwise to solution A and stirred at room temperature for 2 hours to form a transparent solution.
[0048] Solution C was added to the above clear solution and stirred for 15 minutes to obtain a blue solution.
[0049] The blue solution was transferred to a reaction vessel and reacted at 100 °C for 7 hours.
[0050] After cooling to room temperature, the blue precipitate was washed with distilled water and dried at 80°C for 12 hours to obtain Cu(BTC).
[0051] Then Fe@Cu(BTC) is prepared, which specifically includes the following steps:
[0052] 30 mg of Cu(BTC) was dispersed in 20 mL of water and sonicated for 30 min.
[0053] 20 mL of a solution containing 30 mg of PVP was added and stirring was continued at room temperature for 24 hours.
[0054] 0.15 mmol Fe(NO3)3·9H2O and 0.06 mmol H3BTC were added to the above solution and stirring was continued for 2 hours.
[0055] The mixed solution was poured into a three-necked flask and reacted at 95° C. for 12 hours.
[0056] The orange precipitate was washed by centrifugation and dried in vacuo.
[0057] Meanwhile, Fe(BTC) was prepared following similar procedures, but the step of adding Cu(BTC) was removed.
[0058] Then prepare the Fe@Cu(BTC) / SC-Ti3C2 composite material, which specifically includes the following steps:
[0059] 20 mg Ti3C2, 400 mg SC and 10 mg Fe@Cu(BTC) were dispersed in 20 mL distilled water and ultrasonicated for 1 h.
[0060] The SC solution was added dropwise to the Ti3C2 solution and heated in an oil bath at 120°C for 10 min.
[0061] Fe@Cu(BTC) solution was added and the mixture was heated in an oil bath at 120°C to obtain a black suspension.
[0062] N2 was filled in as protective gas and vacuum filtration was performed to obtain black precipitated Fe@Cu(BTC) / SC-Ti3C2 composite material.
[0063] Finally, the Fe@Cu(BTC) / SC-Ti3C2 / GCE electrode was prepared, which specifically included the following steps:
[0064] 2.5 mg of Fe@Cu(BTC) / SC-Ti3C2 black powder was mixed with 0.5 mL of 10% The solutions were mixed and sonicated for 30 min to form a uniform black suspension.
[0065] 8 μL of the suspension was transferred with a pipette and dropped onto the pretreated GCE surface (pretreatment included sequential washing with ethanol and distilled water).
[0066] After standing and drying at room temperature, Fe@Cu(BTC) / SC-Ti3C2 / GCE electrode was obtained.
[0067] At the same time, other component electrodes such as Cu(BTC) / GCE, Fe(BTC) / GCE, Fe@Cu(BTC) / GCE and SC-Ti3C2 / GCE were prepared according to similar steps.
[0068] Based on the above in-depth analysis and considerations, this study first prepared SC-Ti3C2 materials with excellent conductivity and large specific surface area, and successfully loaded bimetallic MOFs (Fe@Cu(BTC)) with a unique core-shell structure on the SC-Ti3C2 substrate through in-situ growth, and finally obtained Fe@Cu(BTC) / SC-Ti3C2 composite materials. This composite material can effectively improve the dispersibility of the two materials, avoid agglomeration between the various materials, provide more active sites, enhance the interaction and contact between the electrode material and the analyte, effectively shorten the transmission path of electrons and ions, and thus significantly improve the electrocatalytic ability of the material. Therefore, the prepared Fe@Cu(BTC) / SC-Ti3C2 composite material exhibits excellent sensing performance in electrocatalytic EP oxidation.
[0069] In addition, in the present invention, in order to further explore and verify the detection efficiency of Fe@Cu(BTC) / SC-Ti3C2 composite material for epinephrine (EP) in human serum in practical applications, another implementation method is provided, and the specific steps are as follows:
[0070] Material preparation and pretreatment:
[0071] First, the Fe@Cu(BTC) core-shell structure material is synthesized, and SC-Ti3C2 (i.e., surface-modified two-dimensional titanium carbide) is introduced through a surface modification strategy to form a Fe@Cu(BTC) / SC-Ti3C2 composite material. This step needs to ensure the uniformity and stability of the composite material for subsequent analysis.
[0072] Prepare 0.1 M phosphate buffer solution (PBS) and adjust its pH to 6.0 for pretreatment of human serum to eliminate impurities or components in the serum that may interfere with EP detection.
[0073] Serum sample processing:
[0074] Collect appropriate amounts of human serum samples from healthy volunteers to ensure that the sample collection, storage, and processing processes comply with medical ethics and biosafety standards.
[0075] The serum samples were diluted and pretreated using pre-prepared 0.1 M PBS (pH = 6.0), the ratio of which was determined according to preliminary experiments, aiming to optimize the detection conditions of EP while maintaining the biological activity of the samples.
[0076] Implementation of standard addition method:
[0077] The standard addition method was used, that is, EP standard solution with known concentration was added to the pretreated serum samples, and multiple concentration gradients were set to simulate actual samples with different EP contents.
[0078] Ensure that there are enough replicates for each concentration gradient to improve data reliability and statistical significance.
[0079] Electrochemical detection:
[0080] The serum samples spiked with different concentrations of EP were tested using differential pulse voltammetry (DPV), a highly sensitive electrochemical technique suitable for quantitative analysis of trace substances.
[0081] During the detection process, it was ensured that the working electrode of the electrochemical workstation was modified with the Fe@Cu(BTC) / SC-Ti3C2 composite material to utilize its excellent electrocatalytic performance and selectivity to improve the detection sensitivity of EP.
[0082] Data Analysis:
[0083] The recovery rate of EP at each concentration gradient was calculated based on the peak current value recorded by the DPV curve. The recovery rate calculation formula is: recovery rate = (measured concentration / added concentration) × 100%.
[0084] At the same time, the relative standard deviation (RSD) at each concentration gradient was calculated to evaluate the precision of the method.
[0085] The recovery rate and RSD were analyzed to evaluate the accuracy and reliability of Fe@Cu(BTC) / SC-Ti3C2 composite materials in detecting EP in actual serum samples.
[0086] Results evaluation and application potential discussion:
[0087] According to the experimental results, the recoveries were between 99.45% and 103.10%, and the RSDs were between 0.82% and 2.98%, indicating that the Fe@Cu(BTC) / SC-T i3C2 composite material had good accuracy and repeatability for the detection of EP in human serum.
[0088] Combined with these results, the potential application of Fe@Cu(BTC) / SC-Ti3C2 composites in practical medical diagnosis, drug monitoring or biomarker analysis is discussed, especially in situations where high sensitivity and selectivity are required.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a highly sensitive adrenaline electrochemical detection electrode, characterized in that: The steps include: S1. 1.5 g of LiF was dispersed in 60 mL of 9 M HCl solution and stirred at room temperature until the white powder was completely dissolved. Then, 1.5 g of MAX (Ti3AlC2) was added to the above solution in small amounts and several times, and slowly stirred at 40 ° C for 48 h. The obtained black suspension was washed with distilled water several times until the pH of the solution reached neutrality. Finally, the obtained precipitate was dispersed in 300 mL of distilled water, and ultrasonicated in an ice bath and N2 atmosphere for 1 h to obtain a black suspension, which was freeze-dried to obtain Ti3AlC2 nanosheets with a few-layer structure. S2. 0.80mmol H3BTC was dissolved in 20mL ethanol solution to obtain solution A, 0.5g PVP was dissolved in 10mL distilled water to obtain solution B, 1.43mmol Cu(NO3)2·3H2O was dispersed in 10mL distilled water to obtain solution C, solution B was added dropwise to solution A, stirred at room temperature for 2h to form a transparent solution, solution C was added to the above transparent solution, stirred for 15min to obtain a blue solution, and finally, it was transferred to a reactor to react under preset reaction conditions, and after waiting to cool to room temperature after the reaction, the obtained blue precipitate was washed with distilled water and dried under preset drying conditions to obtain Cu(BTC); S3. Disperse 30 mg Cu(BTC) in 20 mL water, ultrasonicate for 30 min, add 20 mL 30 mg PVP solution, stir continuously at room temperature for 24 h, then add 0.15 mmol Fe(NO3)3·9H2O and 0.06 mmol H3BTC to the above solution, continue stirring for 2 h, pour the above mixed solution into a three-necked flask for reaction, then centrifuge and wash, vacuum dry the obtained orange precipitate to obtain Fe@Cu(BTC), add 0.15 mmol Fe(NO3)3·9H2O and 0.06 mmol H3BTC to 20 mL 30 mg PVP solution, continue stirring for 2 h, pour the above mixed solution into a three-necked flask for reaction, then centrifuge and wash, vacuum dry the obtained orange precipitate to obtain Fe(BTC); S4. 20 mg Ti3C2, 400 mg SC and 10 mg Fe@Cu(BTC) were dispersed in 20 mL distilled water, respectively, and ultrasonicated for 1 h. Then, the SC solution was added dropwise to the Ti3C2 solution, and heated in an oil bath. The Fe@Cu(BTC) solution was added to the mixed solution, and heated in an oil bath to obtain a black suspension. After the protective gas was filled, vacuum filtration was performed to obtain a black precipitated Fe@Cu(BTC) / SC-Ti3C2 composite material. S5. Mix the above 2.5 mg of Fe@Cu(BTC) / SC-Ti3C2 black powder with 0.5 mL of 10% The solutions were mixed and ultrasonicated for 30 min to form a uniform black suspension. 8 μL of the suspension was pipetted with a pipette and dropped onto the pretreated GCE surface. The suspension was allowed to stand and dry at room temperature to obtain Fe@Cu(BTC) / SC-Ti3C2 / GCE.
2. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S2, the reaction temperature of the preset reaction conditions is 100° C., and the reaction time is 7 hours.
3. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S2, the drying temperature of the preset drying conditions is 80°C and the drying time is 12 hours.
4. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S1, the mass ratio of MAX (Ti3AlC2) to LiF is 1:
1.
5. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S3, the reaction temperature is 95° C. and the reaction time is 12 h.
6. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S4, the heating temperature of the oil bath condition is 120° C., and the heating time is 10 min.
7. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S4, the protective gas is N2.
8. The method for preparing a highly sensitive adrenaline electrochemical detection electrode according to claim 1, characterized in that: In S5, the pretreatment includes washing with ethanol and distilled water in sequence.
9. An application method of a highly sensitive adrenaline electrochemical detection electrode, characterized in that: The invention comprises the use of the detection electrode prepared by the preparation method of any one of claims 1 to 8 in detecting adrenaline.
